Investigação por espectroscopia Mössbauer das fases formadas e sua influência na resistência à corrosão do aço inoxidável austenítico AISI 316L nitretado - Campos, Marcelo (Universidade Federal de São Carlos, 2009)
The plasma nitriding is a technique that improves mechanical and tribological properties of metallic materials as hardness and wear. It improves also the corrosion resistance, because the nitrated layer is formed by phases as the metastable phase (γN), iron nitrides (ε-Fe2-3N and γ -Fe4N) and chrome nitrides. In recent paper studying nitrided AISI 316L stainless steel, we proposed an empiric model to explain the observed results: The higher the ε/γ ratio, better the corrosion resistance is. In order to test this model systematically, we produced samples with ε/γ ratio different values. So, AISI 316L stainless steel samples were nitrided under dc glow discharge, 80 vol. % H2 and 20 vol. % N2 gas mixture, at different conditions of temperature (350º, 400º and 450º C) and time intervals (3, 4 and 5 h). The produced samples were analyzed by X-Ray Diffraction and Mössbauer Spectroscopy, in order to identify the phases presents in the surface layers. The layer thickness was measured by SEM (Scanning Electric Microscope). Besides Hardness Vickers measurements, corrosion performance of the samples was investigated in 3% NaCl aerated electrolytic solution. The present results could not be explained by the first empiric model. Then we proposed a new model: The sample that presents the minimum value for (fórmula) will resist better to corrosion. Besides to explain the presents results, this new model is successful with the previous results. The best condition of treatment was temperature of 400º C, during 4 h, because it produces a sample that presented the best corrosion resistance and a good hardness value.
Keywords: Superficie (Física); Espectroscopia de Mössbauer; Nitretação a plasma; Aço inoxidável; Raio - X - difração; Corrosão; CIENCIAS EXATAS E DA TERRA::FISICA